2017
DOI: 10.1074/jbc.m117.776179
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of isocitrate dehydrogenase 1 (IDH1) mutations identified in tumors: The role of size and hydrophobicity at residue 132 on catalytic efficiency

Abstract: Edited by John M. Denu Isocitrate dehydrogenase 1 (IDH1) catalyzes the reversible NADP؉ -dependent conversion of isocitrate (ICT) to ␣-ketoglutarate (␣KG) in the cytosol and peroxisomes. Mutations in IDH1 have been implicated in >80% of lower grade gliomas and secondary glioblastomas and primarily affect residue 132, which helps coordinate substrate binding. However, other mutations found in the active site have also been identified in tumors. IDH1 mutations typically result in a loss of catalytic activity, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 53 publications
(98 reference statements)
7
90
0
Order By: Relevance
“…Others, however, have found no advantage for the recombinant IDH1 heterodimer (22). Alternatively, the WT dependence might be due to substrate channeling or some other form of cooperativity between the WT and mutant subunits as proposed previously (17,23). Pietrak et al (24) demonstrated that both the WT activity for oxidative decarboxylation of isocitrate and the mutant activity for reduction of ␣-KG to 2-HG remain intact in a WT-mutant IDH1 heterodimer, suggesting that channeling could be involved.…”
mentioning
confidence: 76%
“…Others, however, have found no advantage for the recombinant IDH1 heterodimer (22). Alternatively, the WT dependence might be due to substrate channeling or some other form of cooperativity between the WT and mutant subunits as proposed previously (17,23). Pietrak et al (24) demonstrated that both the WT activity for oxidative decarboxylation of isocitrate and the mutant activity for reduction of ␣-KG to 2-HG remain intact in a WT-mutant IDH1 heterodimer, suggesting that channeling could be involved.…”
mentioning
confidence: 76%
“…6,30 The IDH mutations ( Figure 3A and B) occurring in the catalytic site are likely to cause a loss of catalytic activity; these mutated genes encode for D2HG which is proposed to be an oncometabolite in the cytoplasm for IDH1 and in the mitochondria for IDH2; it competitively inhibits KG-dependent enzymes, including the TET family of 5-methylcytosine hydroxylases and the JmjC family of histones lysine Cancer Informatics demethylases, resulting in cell differentiation. 27,28,31,32 Thirumal Kumar et al 27,28 reveal that the drug therapeutics for D-2hydroxyglutarate dehydrogenase are very limited; therefore, understanding the nature of molecular structure caused by these mutations will serve as platform for the development of novel targets for new drug therapy for D-2-hydroxyglutaric aciduria.…”
Section: Discussionmentioning
confidence: 99%
“…Particular mutations in isocitrate dehydrogenase 1 (IDH1), predominantly at amino acid R132, result in both loss of function of its normal NADPH-generating activity, as well as gain of function of a neomorphic NADPH-consuming activity that produces the oncometabolite 2-hydroxyglutarate (Dang et al, 2009). This change in function was implemented by adding the IDH1-catalyzed neomorphic reaction to Recon3D and imposing turnover numbers of the normal and neomorphic reactions measured by Avellaneda Matteo et al based on the IDH1 mutation status of each tumor (Table S3) (Avellaneda Matteo et al, 2017).…”
Section: Idh1 Mutationsmentioning
confidence: 99%